(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the importance of independent education in the training of qualified specialists in the use of electricity in the national economy, the use of non-traditional methods of electricity generation, radioisotope sources and thermoemission generators.